Desarrollo de un modelo de elementos finitos del conjunto herramienta-sujeción, para su caracterización dinámica en el análisis de vibraciones en el proceso de fresado - Arango Mantilla, Fausto Alberto; Casas Estevez, Felipe (Universidad Antonio Nariño, 2021)
In this finished grade work, a verification of the results was carried out and an own solution of the dynamic behavior of the clamping tool assembly was proposed by a FEM, mentioning the adequate stability regions to avoid the Chatter in the surface finish in the milling processes and Obtain the respective analysis of external forces by means of a simulation in ANSYS, for a face milling process. In this study, the modal behavior is verified to determine the relationship of the dynamic movement in the tool, acting as a tensile stress. Additionally, the harmonium analysis was carried out in natural frequencies for different types of contacts, to determine the regions where resonance and anti-resonance occurs in the system. Taking into account that the type of contact of the tool and tool holder interacts as a friction, spring and rigid contact as a function of a force. Applying external forces on the edges of the tool gives results on the deformation in the face of the tool and the directional deformation in the component (x, y), giving a solution to the Chatter stop that occurs at certain frequencies of oscillation producing resonance when the tool generates cut in the piece of work and analyzing the most stable regions. Where steel is the most significant material for its mechanical properties producing a greater displacement. Keywords: C